PTSD prevalence and factors in intern nursing students after COVID-19 full liberalization in China: a cross-sectional study - Sun, Yuanhao; Li, Xiangdong; Liu, Hairong; Li, Xiaoping; Sun, Lu; Zhang, Lin; Wang, Congzhi; Li, Jing; Liu, Mingming; Zhang, Dongmei; Lei, Yunxiao; Yuan, Ting (Frontiers in Public Health, 2024)
Objective: This study aimed to assess the prevalence of post-traumatic stress disorder (PTSD) and its influencing factors among intern nursing students after the full liberalization of the COVID-19 prevention and control policy in China.: Participants completed the online survey from January 14 to January 19, 2023. A demographic questionnaire, COVID-19 and internship-related questionnaire, the Fear of COVID-19 scale, the Primary Care PTSD Screen, and the Connor-Davidson Resilience Scale were used to conduct the online survey. Result: Of 438 participants, (88.4%) tested positive for COVID-19 in the last 6 months. The prevalence of fear, resilience, and PTSD was 16.9%, 15.5%, and 11.2% respectively. Direct care of COVID patients in hospital (OR =2.084, 95%CI 1.034 4.202), the experience of occupational exposure (OR =2.856, 95%CI 1.436 5.681), working with an experienced team (OR =2.120, 95%CI 1.070 4.198), and fear COVID-19 (OR =8.269, 95%CI 4.150 16.479) were significantly and positively associated with PTSD in nursing internship students. Conclusion: After COVID-19 full liberalization in China, intern nursing students still experienced pandemic-related mental distress, which can bring PTSD. Adequate support and counseling should be provided, as needed, to intern nursing students who are about to enter the workforce and have experienced severe PTSD symptoms related to COVID-19. Our findings indicated that should understand the importance of screening, formulate intervention strategies and preventive measures to address psychosocial problems, and provide coping skills training to intern nursing students.